2019
DOI: 10.17557/tjfc.568326
|View full text |Cite
|
Sign up to set email alerts
|

GENE ACTION AND COMBINING ABILITY FOR NEPS AND SEED COAT NEPS IN COTTON (Gossypium hirsutum L.)

Abstract: Information about heritability and combining ability for neps and seed coat neps is necessary for the cotton breeding strategies. Seven cotton cultivars including 4 lines and 3 testers were mated in line x tester mating design. The 19 genotypes were grown in RCBD with three replications in Aydın-Turkey conditions during 2014 growing season. Non-additive gene action was important in the expression of seed coat nep size, nep count and nep size. The parental lines Carmen and Claudia were good combiners for most n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Abou El -Yazied et al (2014) revealed that ginning out-turn of the second cycle of selection was higher than the base population (13.3% and 17.73%) as a result of two recurrent selection cycles. Zeng and Meredith (2010) and Unay et al (2019) reported genotypic differences for fiber neps and seed coat fragments in cotton. In addition, the correlation among yield and yield components and nep characters were evaluated by Zeng and Meredith (2009), Zeng and Bechere (2012) and Zeng et al (2020).…”
Section: Introductionmentioning
confidence: 99%
“…Abou El -Yazied et al (2014) revealed that ginning out-turn of the second cycle of selection was higher than the base population (13.3% and 17.73%) as a result of two recurrent selection cycles. Zeng and Meredith (2010) and Unay et al (2019) reported genotypic differences for fiber neps and seed coat fragments in cotton. In addition, the correlation among yield and yield components and nep characters were evaluated by Zeng and Meredith (2009), Zeng and Bechere (2012) and Zeng et al (2020).…”
Section: Introductionmentioning
confidence: 99%